2018
DOI: 10.31237/osf.io/4bs2d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Designing the Characteristics of Design Teams via Cognitively Inspired Computational Modeling

Abstract: Teams are a ubiquitous part of the design process and a great deal of time and effort is devoted to managing them effectively. Although teams have the potential to search effectively for solutions, they are also prone to a number of pitfalls. Thus, a greater understanding of teams is necessary to ensure that they can function optimally across a variety of tasks. Teams are typically studied through controlled laboratory experiments or through longitudinal studies that observe teams in situ. However, both of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 217 publications
(320 reference statements)
0
4
0
Order By: Relevance
“…Agent-based modeling often involves imbuing agents with the ability to learn about their environment. Some researchers have modelled social learning by means of mental models [15], or learning from doing the task [17] [13]. While simulating learning, it is often assumed that agents know the design solution space and therefore pursue optimal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Agent-based modeling often involves imbuing agents with the ability to learn about their environment. Some researchers have modelled social learning by means of mental models [15], or learning from doing the task [17] [13]. While simulating learning, it is often assumed that agents know the design solution space and therefore pursue optimal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…These observations show that designers in the cooling system study frequently moved between strategic states, whereas designers in the truss study tended to remain within a state for longer periods. A similar degree of operational restlessness is apparent in nonhidden Markov chain models that are trained on the same data [28].…”
Section: Figure 7 Testing Log-likelihood On Cooling System Study Datmentioning
confidence: 75%
“…This is known as first-order sequencing. While this may initially seem to be a limitation, other work has demonstrated that including multiple previous states does not significantly increase model veracity for Markov-based models in design applications [28]. In addition, evidence from studies of humans solving tavern puzzles has shown that first-order sequencing is important for effective problem-solving [29].…”
Section: Figure 1 Example Of a Hidden Markov Model With Three Statesmentioning
confidence: 99%
“…Most of the models described in the literature deal with some form of learning in their agents to accomplish the purpose of their work. The most common logic implemented in many models listed above is in the form of learning from experience (McComb, 2016;Lapp et al, 2019). However, while simulating learning it is often assumed that the agents are aware of the design solution space and they thrive for the optimal solution (McComb et al, 2017).…”
Section: Generating Solutionsmentioning
confidence: 99%